2013
DOI: 10.1371/journal.pone.0080319
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Trafficking of Endogenously Expressed BMPR2 Mutant Allelic Products in Patients with Heritable Pulmonary Arterial Hypertension

Abstract: More than 200 heterozygous mutations in the type 2 BMP receptor gene, BMPR2, have been identified in patients with Heritable Pulmonary Arterial Hypertension (HPAH). More severe clinical outcomes occur in patients with BMPR2 mutations by-passing nonsense-mediated mRNA decay (NMD negative mutations). These comprise 40% of HPAH mutations and are predicted to express BMPR2 mutant products. However expression of endogenous NMD negative BMPR2 mutant products and their effect on protein trafficking and signaling func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
56
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 52 publications
7
56
0
Order By: Relevance
“…ΔEx2/+ mouse mutation corresponds to an in-frame, extracellular domain, NMD− BMPR2ΔEx2 mutation also described in patients with HPAH, 10,16,20 these findings support our hypothesis that Bmpr2 +/− and Bmpr2 ΔEx2/+ mice model the molecular effects of NMD+ and NMD− BMPR2 mutations, respectively, in patients with HPAH. Our data also show that the level of expression of Bmpr2 in mouse lungs is lower than that in cultured PECs, suggesting that PECs, which constitute only a fraction of the total cells in whole lung, express higher levels of Bmpr2 than the other cellular compartments.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…ΔEx2/+ mouse mutation corresponds to an in-frame, extracellular domain, NMD− BMPR2ΔEx2 mutation also described in patients with HPAH, 10,16,20 these findings support our hypothesis that Bmpr2 +/− and Bmpr2 ΔEx2/+ mice model the molecular effects of NMD+ and NMD− BMPR2 mutations, respectively, in patients with HPAH. Our data also show that the level of expression of Bmpr2 in mouse lungs is lower than that in cultured PECs, suggesting that PECs, which constitute only a fraction of the total cells in whole lung, express higher levels of Bmpr2 than the other cellular compartments.…”
Section: Discussionsupporting
confidence: 89%
“…We compared the severity of experimentally induced pulmonary hypertension (PH) in mice on otherwise identical genetic backgrounds carrying one of two well-characterized heterozygous, splice-site, germ line Bmpr2 mutations that model the effects of known NMD+ and NMD− BMPR2 mutations in patients with HPAH: the out-of-frame Bmpr2ΔEx4-5 mutation [16][17][18][19] and the in-frame, extracellular-domain Bmpr2ΔEx2 mutation. 10,16,20 Previous studies have shown that mice carrying the Bmpr2 ΔEx4-5/+ mutation (which we refer to as Bmpr2 ΔEx2/+ -mutant mice. These studies suggest that the two mutations might confer differential susceptibility to PH in response to chronic hypoxia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of these regulatory mechanisms, modifications related to the biosynthetic maturation of TGFb-SF receptors have been relatively less studied. The importance of regulation of such receptors at early stages of folding, maturation and trafficking is exemplified by the molecular fate of receptors carrying genetic disease-related mutations, which induce the intracellular retention of AMHRII and the type-II BMP receptor (BMPRII, also known as BMPR2), and abolish the signaling response to their respective ligands (Belville et al, 2009;Faure et al, 1996;Frump et al, 2013;Li et al, 2010;Sobolewski et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the next step for PAH management may be the development of causal mutation-specific therapies. Frump and colleagues have demonstrated that it is possible to restore the TGF-b activity in cells carrying an in-frame deletion of exon 2 of the BMPR2 gene by improving trafficking of the mutated protein using chemical chaperones [28]. These authors speculated that chemical chaperones could be beneficial for all carriers of a missense BMPR2 mutation or an in-frame large rearrangement which affects the trafficking of the protein to the cell surface.…”
mentioning
confidence: 99%